Time Perspective and Experience of Depression, Stress, and Loneliness Among Adolescents in Youth Educational Centres - Anna Dąbrowska; Joanna Marek-Banach; Philip Zimbardo; Agata Łopatkiewicz; Ewa Wysocka (Nicolaus Copernicus University in Toruń, 2022)
Time perspective is of key significance in overcoming an identity crisis in adolescence. Re- search using the Zimbardo Time Perspective Inventory (ZTPI) was conducted on a group of 311 adolescents (aged 13-18) in several youth educational centres in south-eastern Poland. The research was designed to identify the significance of time perspective when it comes to levels of depression, stress and loneliness experienced in conditions of institutional rehabil- itation and education. Linear regression analysis demonstrated the following: a positive past focus reduces the intensity of anxiety and depression; a positive past and future focus results in reduced depression, loneliness and stress; the experience of stress combined with depression enhances the significance of time perspective for the feeling of loneliness; and a low level of family loneliness reduces depression.